Nivel de conocimiento y actitudes hacia el examen de papanicolaou en gestantes del Hospital León Becerra de Milagro. noviembre 2023 - abril 2024. - Mejía Urdanigo, Ayleen Noelia (2024)
Introduction: Cervical cancer is preventable through cervical cytology, but it remains a public health challenge. At the León Becerra de Milagro Hospital, an investigation was carried out to evaluate the level of knowledge and attitudes towards the Pap test in 80 pregnant women. It was found that, although the majority had heard about the exam, a significant percentage was unaware of its purpose and recommended frequency. Objective: The objective was to determine the level of knowledge and attitude towards the Pap test in pregnant women treated in the gynecological emergency area of the León Becerra de Milagro Hospital in the months of November 2023 to April 2024. Materials and Methods: It was carried out carried out an observational, descriptive and transversal research. Surveys were applied to 80 pregnant women at the León Becerra de Milagro Hospital. Demographic data and responses related to knowledge and attitudes toward Pap testing were analyzed. Results: It was found that 56% of pregnant women had heard about the Pap test, but 36% did not know its purpose and 40% did not know the recommended frequency. Regarding attitudes, 53% believed that the test should be avoided during pregnancy and 45% were afraid of a negative diagnosis. Conclusions: There remains a significant lack of knowledge about the Pap test among pregnant women, which could affect their participation in the prevention of cervical cancer. Furthermore, attitudes and knowledge influence decision-making to ensure better well-being. It is necessary to implement adapted educational campaigns and improve access to the exam to reduce barriers and promote greater participation in its prevention.